Enhancing Financial Literacy in Young Adults: An Android-Based Personal Finance Management Tool - Riswandha Imawan; Wahyu Permana Putra; Rabee Alqahtani; Emmanouil D. Milakis; Mykhailo Dumchykov (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
This study details the design, development, and evaluation of an Android-based personal finance management application tailored for young adults in higher education. Addressing unique financial challenges such as limited experience and fluctuating income, the application incorporates features like income tracking, expense monitoring, budgeting, and financial goal setting. Developed using the Waterfall model, the application includes secure login systems, intuitive transaction management, customizable goals, budget projections, and automated notifications to encourage financial discipline. Usability evaluations using a 5-point Likert scale with 50 users revealed an overall satisfaction score of 4.6/5, rated 'Excellent.' Users praised the intuitive design, accurate tracking, and motivational reminders, while also suggesting additional customization and deeper financial analysis for future updates. This study demonstrates the potential of targeted digital tools to foster financial literacy and resilience, offering evidence that personalized technology can significantly improve financial behaviors in young adults. Future research will explore enhanced customization and AI-driven features to further refine the application’s impact.